2021
DOI: 10.3389/fonc.2021.607531
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Related Adverse Events and Their Association With the Effectiveness of PD-1/PD-L1 Inhibitors in Non-Small Cell Lung Cancer: A Real-World Study From China

Abstract: BackgroundProgrammed cell death-1/programmed cell death ligand-1 (PD-1/PD-L1) inhibitors are increasingly used in China, but no real-world data are available about the immune-related adverse events (irAEs). This real-world retrospective study aimed to assess the safety and effectiveness of PD-1/PD-L1 inhibitors in patients with non-small cell lung cancer (NSCLC) and to analyze the association between irAEs and effectiveness.MethodsThis was a retrospective study of the clinical data of patients with NSCLC treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 44 publications
5
31
0
1
Order By: Relevance
“…Of whom, the incidence of adverse reaction with grade ≥3 was only 16.2%, which indicated that the regimen of PD-1 inhibitor administration was acceptable and manageable. And the safety profile in our study was consistent with the adverse reactions of the previous retrospective study regarding PD-1 blockades in patients with advanced NSCLC [8]. However, some immunotherapyrelated adverse reactions should be paid more attention to the elderly patients who received PD-1 inhibitor monotherapy [37].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Of whom, the incidence of adverse reaction with grade ≥3 was only 16.2%, which indicated that the regimen of PD-1 inhibitor administration was acceptable and manageable. And the safety profile in our study was consistent with the adverse reactions of the previous retrospective study regarding PD-1 blockades in patients with advanced NSCLC [8]. However, some immunotherapyrelated adverse reactions should be paid more attention to the elderly patients who received PD-1 inhibitor monotherapy [37].…”
Section: Discussionsupporting
confidence: 88%
“…To our knowledge, the occurrence of NSCLC increased with age and previous work suggested that the onset age of the diagnosis of NSCLC in clinical practice was approximately 70 years old [7]. Additionally, regarding the epidemiological data in China, a previous real-world study demonstrated that the proportion of patients older than 65 years old was 35.1%, highlighting that the proportion of elderly cases (>65 years) among all NSCLC patients in China was over 35% [8]. Unfortunately, given that most clinical trials set strict age screening criteria (usually <75 years), the proportion of patients over the age of 75 who were able to participate in clinical trials was probably less than 10% [9], resulting in limited available evidence as clinical guidelines among elderly patients with NSCLC [10].…”
Section: Introductionmentioning
confidence: 76%
“…Another clinically important and controversial issue is the relationship between irAE and patient survival (41). Earlier studies in melanoma and NSCLC had shown conflicting results, namely favorable (41)(42)(43)(44)(45) or indifferent outcome for patients developing irAEs (46)(47)(48), which was in part due to different handling of the "immortal-time bias" (ITB, aka A B FIGURE 4 | Progression-free and overall survival by occurrence of irAEs in a 14-week landmark analysis. (A) The median PFS under immunotherapy was 10 months (8.7-11.4) for patients without irAE vs. 17 months (10.3-23.6, logrank p = 0.003) for patients with irAEs in a 14-week landmark analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Another clinically important and controversial issue is the relationship between irAE and patient survival ( 41 ). Earlier studies in melanoma and NSCLC had shown conflicting results, namely favorable ( 41 45 ) or indifferent outcome for patients developing irAEs ( 46 48 ), which was in part due to different handling of the “immortal-time bias” (ITB, aka “guaranteed-time bias”) by the various investigators ( 49 ). In a recent meta-analysis, both the confounding effect of the ITB and the real, positive association between irAE and patient survival that remains significant after control for ITB could be shown ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that the development of irAEs after ICI treatment was associated with a better response and survival. [44,45] However, this association may be biased by differences in histological subtype, disease burden, and lines of treatment. We focused our analyses on TRAEs and irAEs with ICIs, providing detailed data for clinicians which will be helpful when choosing different treatment regimens with regards to both e cacy and safety.…”
Section: Discussionmentioning
confidence: 99%